Treatment of wastewater sludge by liquid state bioconversion process - Alam, Md. Zahangir; Fakhru'l-Razi, A; Mollah, Abul Hussain; Roychoudhary, P. K. (Marcel Dekker, Inc., 2001)
This study was conducted to evaluate the eﬀect of an eminent decay fungus, Phanerocheate chrysosporium of organic residues on wastewater sludge for its improvement through decomposition and separation of waste particles by Liquid State Bioconversion (LSB). The eﬀect of fungal treatment was compared to uninoculated (Control) at three dif- ferent harvests 7, 14 and 21 days after inoculation (DAI). The observed results showed that the weight loss and solid content of wastewater sludge were signiﬁcantly inﬂuenced by Phanerocheate chrysosporium. Both para- meters were highly inﬂuenced at 7 DAI. The COD and pH of wastewater sludge were also highly inﬂuenced by fungal treatment.